Daphneodorins A–C, Anti-HIV Gnidimacrin Related Macrocyclic Daphnane Orthoesters from Daphne odora - Otsuki, Kouharu; Li, Wei; Asada, Yoshihisa; Chen, Chin-Ho; Lee, Kuo-Hsiung; Koike, Kazuo (Organic letters, 2020)
Three novel gnidimacrin related macrocyclic daphnanes (GMDs), daphneodorins A–C (2–4), were isolated from Daphne odora Thunb., together with gnidimacrin (1). Their structures were established by extensive physicochemical and spectroscopic analyses. Compounds 2 and 3 potently inhibited HIV-1 replication at subnanomolar concentrations (EC50 0.16 and 0.25 nM, respectively). Compounds 2–4 represent a novel type of GMDs that are highly oxygenated on the macrocyclic ring, suggesting good potential for anti-HIV drug development by further chemical modification.